2022
DOI: 10.3847/1538-3881/ac517f
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Alignment Between the Orbits of Planetary Systems and their Visual Binary Companions

Abstract: Astronomers do not have a complete picture of the effects of wide-binary companions (semimajor axes greater than 100 au) on the formation and evolution of exoplanets. We investigate these effects using new data from Gaia Early Data Release 3 and the Transiting Exoplanet Survey Satellite mission to characterize wide-binary systems with transiting exoplanets. We identify a sample of 67 systems of transiting exoplanet candidates (with well-determined, edge-on orbital inclinations) that reside in wide visual binar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 121 publications
5
19
0
Order By: Relevance
“…Like the DS Tuc AB system (Newton et al 2019), the orbit of the binary is aligned with that of the planetary orbit. This follows the trend from Christian et al (2022) that wide transiting planet-hosting binaries with separations between 100-700 au are preferentially found in edge-on orbits. Christian et al (2022) suggest that such trends may be due to the companions being formed from disk fragmentation, or the realignment of the inner disk by the perturbing outer companion.…”
Section: Summary and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Like the DS Tuc AB system (Newton et al 2019), the orbit of the binary is aligned with that of the planetary orbit. This follows the trend from Christian et al (2022) that wide transiting planet-hosting binaries with separations between 100-700 au are preferentially found in edge-on orbits. Christian et al (2022) suggest that such trends may be due to the companions being formed from disk fragmentation, or the realignment of the inner disk by the perturbing outer companion.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…This follows the trend from Christian et al (2022) that wide transiting planet-hosting binaries with separations between 100-700 au are preferentially found in edge-on orbits. Christian et al (2022) suggest that such trends may be due to the companions being formed from disk fragmentation, or the realignment of the inner disk by the perturbing outer companion. The efforts by TESS follow-up teams to provide diffraction limited imaging of a majority of planet candidates, such as HIP 94235, will help probe the continuation of this trend to <100 au separations.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…Indeed, observational studies have shown that the occurrence rate of exoplanets in stellar binaries tends to be smaller than those of wider binaries or single stars (e.g., Wang et al 2014;Kraus et al 2016;Moe & Kratter 2021;Ziegler et al 2021). Moreover, the orbits of planet-hosting stellar binaries appear to be statistically aligned with those of the planets, while orbital inclinations of binaries without planets are likely isotropic (e.g., Behmard et al 2022;Christian et al 2022;Dupuy et al 2022). The orbital alignment between binaries and planets could be primordial if both stellar components and the planets all form within the same massive disk or hierarchical cloud fragmentation that preserves orbital angular momenta (e.g., Sigalotti et al 2018;Tokovinin 2018;Christian et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We applied this method to twin wide binaries and showed that they are highly eccentric (Hwang et al 2022a), suggesting that they were formed at smaller separations and their orbits were widened by subsequent interaction with the environments (El-Badry et al 2019). If one of the component star is an eclipsing binary or has a transiting planet, then v-r angles can constrain the orbital alignments between the outer companions and the inner eclipsing or transiting systems (Behmard et al 2022;Cañas et al 2022;Christian et al 2022).…”
Section: Hwangmentioning
confidence: 99%